Morphology and ontogeny of carpus and tarsus in stereospondylomorph temnospondyls - Witzmann, Florian; Fröbisch, Nadia (PeerJ, 2023)
Skeletal development is well known in temnospondyls, the most diverse group of Paleozoic and Mesozoic amphibians. However, the elements of carpus and tarsus (i.e., the mesopodium) were always the last bones to ossify relative to the other limb bones and with regard to the rest of the skeleton, and are preserved only in rare cases. Thus, in contrast to the other parts of the limb skeleton, little is known about the ontogeny and sequence of ossification of the temnospondyl carpus and tarsus. We intended to close this gap by studying the ontogenies of a number of Permo/Carboniferous stereospondylomorphs, the only temnospondyls with preserved growth series in which the successive ossification of carpals and tarsals can be traced. Studying the degree of mesopodial ossification within the same species show that it is not necessarily correlated with body size. This indicates that individual age rather than size determined the degree of mesopodial ossification in stereospondylomorphs and that the largest individuals are not necessarily the oldest ones. In the stereospondylomorph tarsus, the distal tarsals show preaxial development in accordance with most early tetrapods and salamanders. However, the more proximal mesopodials exhibit postaxial dominance, i.e., the preaxial column (tibiale, centrale 1) consistently started to ossify after the central column (centralia 2–4, intermedium) and the postaxial column (fibulare). Likewise, we observed preaxial development of the distal carpals in the stereospondylomorph carpus, as in most early tetrapods for which a statement can be made. However, in contrast to the tarsus, the more proximal carpals were formed by preaxial development, i.e., the preaxial column (radiale, centrale 1) ossified after the central column (centralia 2–4, intermedium) and before the postaxial column (ulnare). This pattern is unique among known early tetrapods and occurs only in certain extant salamanders. Furthermore, ossification proceeded from distal to proximal in the central column of the stereospondylomorph carpus, whereas the ossification advanced from proximal to distal in the central column of the tarsus. Despite these differences, a general ossification pattern that started from proximolateral (intermedium or centrale 4) to mediodistal (distal tarsal and carpal 1) roughly in a diagonal line is common to all stereospondylomorph mesopodials investigated. This pattern might basically reflect the alignment of stress within the mesopodium during locomotion. Our observations might point to a greater variability in the development of the mesopodium in stereospondylomorphs and probably other early tetrapods than in most extant tetrapods, possibly mirroring a similar variation as seen in the early phases of skeletogenesis in salamander carpus and tarsus.
Keywords: Limb development; Ossification; Carpus; Tarsus; Tetrapod; Postaxial; Preaxial; Stereospondyl